Giving and responding to feedback through visualisations in design critiques. Issue 1 (2nd April 2016) - Tolbert, DeLean; Buzzanell, Patrice M.; Zoltowski, Carla B.; Cummings, Antonette; Cardella, Monica E.
Abstract: Designers develop skills and knowledge through experience and feedback – feedback from colleagues, clients, supervisors, users, stakeholders, or the success or failure of a solution and design instructors. However, the design coaches (instructors and industry clients) and design students must negotiate ambiguity in the feedback process. In this article, we investigate visualisation within a design critique setting, where the industrial design instructor and the students are navigating ambiguity while the instructor is providing feedback on the design work. Using a constitutive research approach, we investigate the relationships among visualisation, ambiguity and critique, where each of these components offers a lens into understanding how designers use the tensions within ambiguity and clarity to achieve designs that fulfil assignments or other purposes. As part of this process, we characterise differences between the ways the instructor and the student interact with the human and non-human agents. The negotiations of ambiguity among human and non-human agents through and within the constitutive processes of visualisation offers fresh insights into how design is accomplished as well as how visualisation can be expanded productively in design education contexts.